A Reflection on the Collapse of the Power of the Church and the Rise of Science Authority - Fathor Rasi (SIASAT, 2020)
This article explains that the Modern period marked by the collapse of the power of the church and the rise of science authority. At the next phase, the new image of man becomes inevitable. After modernist philosophers called on people to go away from the church, science in turn lock and catch the man, then he is traped in factories and industries. Substantive dimensions in man is eliminated, so that his presence in the world is subordinated by the industrial machines. Human in modern world is not more than a "the screw of industry.